Adopting International Financial Reporting Standards for Small and Medium‐sized Enterprises. Issue 2 (June 2015) - Chand, Parmod; Patel, Arvind; White, Michael
<x xml:space="preserve">Abstract</x> Diverse complications and controversial issues in the adoption of International Financial Reporting Standards (IFRS) for Small and Medium‐sized Enterprises (SMEs) have been reported by many jurisdictions, prompting them not to adopt this set of standards. Conversely many jurisdictions have adopted or are in the process of adopting IFRS for SMEs. This study considers the impetus for successfully achieving accounting convergence with IFRS for SMEs in those jurisdictions. The possible transition issues that may arise when countries adopt IFRS for SMEs are also highlighted. Furthermore, to provide pioneering evidence on the problems accountants encounter when applying IFRS for SMEs, we conduct a survey on accounting practitioners in Fiji – an early adopter of this set of standards. Both the insights provided on the process of embracing IFRS for SMEs in Fiji and the opinions elicited from accountants highlight new dimensions to the inherent problems in IFRS for SMEs. Scant attention has been given to this issue so far; hence the empirical evidence provided by our study informs not only the global convergence of SME accounting but also the quality of the current suite of IFRS for SMEs.